2001
DOI: 10.1172/jci11380
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes are important in early atherosclerosis

Abstract: Lymphocytes represent a potentially important proinflammatory cell that localizes to atherosclerotic lesions. To determine whether they contribute to lesion development, atherosclerosis-prone (LDLR -/-) mice were crossed with lymphocyte-deficient (RAG1 -/-) mice to generate double knockout progeny. After 8 weeks on a Western-type diet (WTD), lesion development was reduced by 54% in double knockout mice, as compared with matched LDLR -/-controls. However, these significant differences in lesion area gradually s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 54 publications
6
98
1
4
Order By: Relevance
“…Th1 adaptive responses, and Th1 cytokines in particular have been shown to play a key role in promoting atherogenesis (17,(35)(36)(37). In contrast, we now demonstrate that immunization with MDA-LDL directly triggers an antigen-specific Th2 response that is associated with an atheroprotective effect.…”
Section: Discussionmentioning
confidence: 57%
“…Th1 adaptive responses, and Th1 cytokines in particular have been shown to play a key role in promoting atherogenesis (17,(35)(36)(37). In contrast, we now demonstrate that immunization with MDA-LDL directly triggers an antigen-specific Th2 response that is associated with an atheroprotective effect.…”
Section: Discussionmentioning
confidence: 57%
“…As yet, robust mouse models for lesion rupture and thrombosis have not been developed, but recent observations by several laboratories suggest that apoE-null or LDL receptor (LDLR)-null mice can develop lesions that share many of the features of advanced human lesions and that might be capable of rupture. [15][16][17][18] Molecular studies have also suggested potential mechanisms that could contribute to unstable plaque formation in mice. 19 -21 The first linkage studies of atherosclerosis susceptibility in mice were carried out with RI strains derived from susceptible strains, such as C57BL/6J, and resistant strains, such as C3H/HeJ, BALB/cJ, and A/J.…”
Section: Mapping Genes For Atherosclerosis In Micementioning
confidence: 99%
“…[1][2][3] The pathogenic role of T cells in atherosclerosis is well described in animal models. [4][5][6][7] Recently, the association of pathogenic T cells with acute coronary syndrome in humans was addressed. [8][9][10] However, it remains unclear which specific subpopulation of T cells plays a major role in acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%